Endovascular Thrombectomy Versus Best Medical Management in Patients With Large Vessel Occlusion Stroke Presenting Beyond 24 Hours: Results From the TRACK‐LVO Late Multicenter Cohort - Yongbo Xu; Shuling Liu; Adnan I. Qureshi; Pinyuan Zhang; Xiaochen Zhang; Shuai Liu; Yuanyuan Xue; Fanlei Meng; Guodong Xu; Yongchang Liu; Youquan Gu; Yibin Cao; et al. (Stroke: Vascular and Interventional Neurology)
Background The efficacy and safety of endovascular thrombectomy (EVT) performed beyond 24 hours from the last known well remain uncertain. This study aims to investigate the potential benefits of EVT versus best medical management (BMM) beyond 24 hours. Methods TRACK‐LVO Late (Late Triage of Patients Presenting Beyond 24 Hours With Acute Ischemic Stroke Due to Large Vessel Occlusions) is an ongoing, multicenter, prospective cohort study. A total of 410 individuals met the inclusion and exclusion criteria and were included in the cohort analyses from 2018 to 2024. The primary outcome was functional independence, defined as a modified Rankin Scale score of 0–2 at 90 days. Safety outcomes included all‐cause mortality within 90 days and symptomatic intracranial hemorrhage. A propensity score analysis was conducted to adjust for baseline imbalances. The association between treatment and primary outcome/safety outcomes was assessed using logistic regression, adjusted for age, sex, National Institutes of Health Stroke Scale score, premorbid modified Rankin Scale score, occlusion sites, and time from onset to admission. Results Among the 410 patients, 209 were in the EVT group and 201 in the BMM group. The EVT group showed higher odds of functional independence in the propensity score‐matched cohort (adjusted odds ratio, 4.13 [95% CI, 2.42–7.05]; P<0.001). No significant difference in mortality rate was observed between groups (adjusted odds ratio, 1.59 [95% CI, 0.60–4.25]; P = 0.354). However, the EVT group had an increased risk of symptomatic intracranial hemorrhage compared with the BMM group (adjusted odds ratio, 8.72 [95% CI, 1.04–73.10]; P = 0.046). These findings were consistent in sensitivity analyses using propensity score inverse probability of treatment weighting. Conclusion EVT performed after 24 hours from the last known well was associated with higher rates of functional independence compared with BMM and demonstrated acceptable safety. High‐quality randomized trials are needed to further compare EVT and BMM beyond 24 hours from the last known well.